A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile - Barahona-Segovia, Rodrigo M.; Barceló, Matías (Zootaxa, 2019)
The Neotropical region has a high species richness of flower flies. However, there are many known species awaiting proper description. Cepa Thompson & Vockeroth is a Neotropical genus with scattered records and few individuals collected of its three species. In the present study, a female of a new species of Cepa is described, C. simonettii Barahona-Segovia sp. nov., from the Valdivian evergreen forest representing the first record of this genus in Chile. In addition, an identification key to all known species of Cepa is provided. Morphological and biogeographic aspects of this new Cepa species are discussed, as well as the potential phylogenetic relationship with other members of Merodontini.